2009
DOI: 10.1002/jcu.20658
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis of postpartum pseudoaneurysms of the uterine artery: A report of 2 cases

Abstract: Two cases of post-partum uterine artery pseudoaneurysm are described, 1 after normal vaginal delivery and the other after Caesarean section. Both cases were complicated by heavy bleeding and treated with catheter embolization. A turbulent arterial-type velocity waveform with high peak velocity and forward end-diastolic flow was registered in the feeding vessel. The peak blood flow velocity was high in both cases. The resistance index in the uterine artery was lower in the affected side of the uterus. Three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…40 Vascular abnormalities of the uterus have recently been described as possibly more common causes of severe SPH than previously thought. [25][26][27][28][29][30][31] In a Cochrane Review, Alexander et al 50 identified 45 papers about the management of SPH and concluded that little information is available from randomized trials to guide clinicians in the management of this condition. Since, the causes of SPH may be numerous, the best treatment options should be chosen according to the underlying cause of bleeding.…”
Section: Retained Placental Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…40 Vascular abnormalities of the uterus have recently been described as possibly more common causes of severe SPH than previously thought. [25][26][27][28][29][30][31] In a Cochrane Review, Alexander et al 50 identified 45 papers about the management of SPH and concluded that little information is available from randomized trials to guide clinicians in the management of this condition. Since, the causes of SPH may be numerous, the best treatment options should be chosen according to the underlying cause of bleeding.…”
Section: Retained Placental Tissuementioning
confidence: 99%
“…25,81 In contrast, acquired AV abnormalities of the uterus are associated with trauma after previous intrauterine procedures, RPT, infection or malignancy and are more common. [26][27][28][29][30][31] The difference between normal perivillous blood flow increased myometrial flow related to RPT and AV malformations seems to be difficult. 25,47,81 Three typical ultrasound signs of pseudoaneurysm include: A pulsating hypoechoic area connected to feeding artery by a narrow neck on Gray-scale ultrasound, a turbulent flow inside the pseudoaneurysm on color Doppler and a reversed flow on the neck of the pseudoaneurysm on pulse Doppler.…”
Section: Uterine Arteriovenous Lesions (True Av Malformations Acquirmentioning
confidence: 99%
See 1 more Smart Citation
“…The main primary causes are uterine atony (∼70% of cases), retained placental fragments, endometritis, genital laceration, uterine inversion or rupture, and coagulation disorders. Delayed postpartum hemorrhage, affecting 1∼3% of deliveries, occurs 24 h to 6 weeks postpartum and is usually due to endometritis, retained products of conception, or sloughing of the placental site eschar, and vascular abnormalities affecting the myometrial circulation (arterial aneurysm, pseudoaneurysm, and arteriovenous malformations) (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this is the first case report in literature of a mycotic aneurysm of the proximal uterine artery that has been successfully embolized [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%